2009
DOI: 10.1111/j.1399-5448.2008.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

The PedsQL™ Multidimensional Fatigue Scale in type 1 diabetes: feasibility, reliability, and validity

Abstract: The results demonstrate the measurement properties of the PedsQL Multidimensional Fatigue Scale in type 1 diabetes. The findings suggest that the PedsQL Multidimensional Fatigue Scale may be utilized in the standardized evaluation of fatigue in pediatric patients with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 31 publications
6
66
2
1
Order By: Relevance
“…Results of this pilot study showed that CHL experienced significantly more fatigue across all domains than the control group. A somewhat unexpected finding was that the CHL reported more fatigue on the PedsQL-MFS than children with other health conditions commonly associated with fatigue, such as cancer, rheumatoid arthritis, diabetes, and obesity (Varni et al, 2002;Varni, Burwinkle, & Szer, 2004;Varni, Limbers, Bryant, & Wilson, 2009. While Hornsby et al provided empirical support for the idea that CHL are at increased risk for fatigue, the preliminary study had several limitations.…”
Section: Subjective Fatigue In Chlmentioning
confidence: 83%
See 3 more Smart Citations
“…Results of this pilot study showed that CHL experienced significantly more fatigue across all domains than the control group. A somewhat unexpected finding was that the CHL reported more fatigue on the PedsQL-MFS than children with other health conditions commonly associated with fatigue, such as cancer, rheumatoid arthritis, diabetes, and obesity (Varni et al, 2002;Varni, Burwinkle, & Szer, 2004;Varni, Limbers, Bryant, & Wilson, 2009. While Hornsby et al provided empirical support for the idea that CHL are at increased risk for fatigue, the preliminary study had several limitations.…”
Section: Subjective Fatigue In Chlmentioning
confidence: 83%
“…Parent versions of the PedsQL-MFS are also available. The PedsQL-MFS was developed for children and adolescents with different chronic conditions such as cancer, rheumatoid arthritis, diabetes, cerebral palsy, and obesity (Varni et al, 2006(Varni et al, , 2002(Varni et al, , 2009(Varni et al, , 2010. The test was not developed for CHL and does not include items weighted for fatigue potentially associated with sustained listening, attending, concentrating, or processing speech in difficult listening conditions.…”
Section: Fatigue Measurementioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly used fatigue measure was the Paediatric Quality of Life Inventory Multidimensional Fatigue Scale (PedsQL-MFS), a well-validated measure of general fatigue, cognitive fatigue, and sleep/ rest fatigue that can be rated both by patients and by their parents. 14,31,32 Considering self-reports on the PedsQL-MFS, general fatigue ranged from 14% to 56%, sleep/rest fatigue from 12% to 38%, and cognitive fatigue from 9% to 52%. Parent-reports of their offspring's general fatigue ranged from 27% to 63%, sleep/rest fatigue from 35% to 63%, and cognitive fatigue from 23% to 76%.…”
Section: Overview Of Fatiguementioning
confidence: 99%